De vrouw en de kunstenaar. - D'Haese, Jan; Hof ter Nederloo, Sint-Pieters-Leeuw; BBL (Bank Brussel Lambert) Brussel (Sint-Pieters-Leeuw : De Vrienden van Nederloo, 1986)
Bekaert, Piet ; Blondeel, Armand ; Burssens, Jan ; De Bruyne, Dees ; Driesschaert, Herwig ; Dyckmans, Bruno ; Leclercq, Guy ; Slabbinck, Rik ; Theys, Yvan ; Van Cauwenbergh, Marc ; Vander Eycken, Robert ; Van Groeningen, Benny ; Verstraete, Luc
De vrouw en de kunstenaar, Hof ter Nederloo, Sint-Pieters-Leeuw, 10 oktober - 16 november 1986
boek